2021
DOI: 10.1007/s00338-021-02124-8
|View full text |Cite
|
Sign up to set email alerts
|

Two offshore coral species show greater acclimatization capacity to environmental variation than nearshore counterparts in southern Belize

Abstract: Coral reefs are enduring decline due to the intensifying impacts of anthropogenic global change. This widespread decline has resulted in increased efforts to identify resilient coral populations and develop novel restoration strategies. Paramount in these efforts is the need to understand how environmental variation and thermal history affect coral physiology and resilience. Here, we assess the acclimatization capacity of Siderastrea siderea and Pseudodiploria strigosa corals via a 17-month reciprocal transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
2
7
1
Order By: Relevance
“…Population genetic data support the lack of local adaptation with gene flow along both the horizontal and vertical axes of the fjord 49 . Similar results of local acclimatisation have been shown for calcification rates of the gorgonian coral Antillogorgia bipinnata 88 and several tropical coral species 89 , 90 after reciprocal transplantation. The morphological change of the native and novel deep corals on the pulley in the water column is also a sign of acclimatisation to the environmental conditions in deep waters.…”
Section: Discussionsupporting
confidence: 80%
“…Population genetic data support the lack of local adaptation with gene flow along both the horizontal and vertical axes of the fjord 49 . Similar results of local acclimatisation have been shown for calcification rates of the gorgonian coral Antillogorgia bipinnata 88 and several tropical coral species 89 , 90 after reciprocal transplantation. The morphological change of the native and novel deep corals on the pulley in the water column is also a sign of acclimatisation to the environmental conditions in deep waters.…”
Section: Discussionsupporting
confidence: 80%
“…Varying levels of plasticity in P. strigosa and P. astreoides from different habitats has been previously reported [47,88]; however, natal reef effects were not evident in either species in this study (Fig 3B and 3C). The small sample size of P. strigosa likely contributed to the lack of differences between habitats, while different measures of plasticity-physiological plasticity (present study) vs. gene expression plasticity [88]-may contribute to the inconsistent responses observed in P. astreoides.…”
Section: Global Change and Species-specific Drivers Of Physiological ...supporting
confidence: 54%
“…affects responses to global change. Specifically, the inshore site is known to be more environmentally variable (i.e., diel and seasonal variability) than the offshore location (S1 Fig), potentially diving local adaptation and/or long-term acclimatisation in these species [46][47][48]. This study further investigates the physiological responses of corals assessed in Bove et al [17] and detailed descriptions of experimental setup can be found there.…”
Section: Experimental Designmentioning
confidence: 96%
See 1 more Smart Citation
“…Protein concentration in the host fraction was measured on a spectrophotometer (BioTek ELx808, Agilent) using the Bradford method. Total host lipids were measured colorimetrically on a spectrophotometer (BioTek PowerWave XS2, Agilent) as described [51]. Surface area was determined by the single wax dipping method [52].…”
Section: Physiological Analysesmentioning
confidence: 99%